"Am I intruding?": Amateur videos and the need to regulate it - Tanbengco, Hency L. (Animo Repository, 2015)
The purpose of this study is to show how the taking of amateur videos could lead to privacy rights violations, and that the law as it is now is inadequate to give remedy to the offended party. There has already been an incident involving an amateur video, and no one anticipated how far the damage would reach. While the general idea of encouraging individuals to record newsworthy events seems like a good idea, and might even be considered a civic duty in line with potentially reporting unlawful incidents to the proper authorities, it should not violate a person’s reasonable expectations of privacy. More so, there should be a remedy available in law for an offended party if said party wants to go after the video taker for causing damage to their person.